2009
DOI: 10.1093/humrep/dep119
|View full text |Cite
|
Sign up to set email alerts
|

Daily variation of brain-derived neurotrophic factor and cortisol in women with normal menstrual cycles, undergoing oral contraception and in postmenopause

Abstract: BDNF has a diurnal variation in women that is somewhat analogous to cortisol variation; however, the amplitude of the variation in BDNF levels appears to be influenced by ovarian function. Interactions between BDNF, the hypothalamus-pituitary-adrenal axis and sex steroids might play a critical role in the human homeostasis and adaptation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 41 publications
7
70
0
Order By: Relevance
“…In particular, during the follicular phase of the menstrual cycle and after menopause, plasma BDNF values were reported to be higher in the morning (8:00 h), followed by a substantial decrease throughout the day, with the lowest values observed at midnight [17]. According to our findings, the diurnal variation of plasma BDNF in FHA showed lower levels than in eumenorrheic women at any sampling time, and interestingly, normal daily variations of BDNF disappeared in FHA patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, during the follicular phase of the menstrual cycle and after menopause, plasma BDNF values were reported to be higher in the morning (8:00 h), followed by a substantial decrease throughout the day, with the lowest values observed at midnight [17]. According to our findings, the diurnal variation of plasma BDNF in FHA showed lower levels than in eumenorrheic women at any sampling time, and interestingly, normal daily variations of BDNF disappeared in FHA patients.…”
Section: Discussionmentioning
confidence: 99%
“…This method has a detection limit of 15.6 pg/ml and intra- and interassay variation coefficients of 6.0 and 8.5%, respectively. We used a highly specific antiserum, which indicates <3.0% cross-reactivity with other related neurotrophic factors (NGF, NT-3, NT-4) at a concentration of 100 ng/ml, as specified in the manufacturer's notes [17]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether local oestradiol produced by granulosa cells within the ovary also alters extraneuronal neurotrophin expression remains to be determined. However, it has been shown that circulating levels of oestradiol are positively associated with BDNF concentrations in women undergoing fertility treatment (Monteleone et al 2007), and plasma BDNF levels fluctuate during a menstrual cycle (Cubeddu et al 2011), declining in post-menopausal women (Lommatzsch et al 2005, Pluchino et al 2009), but can be increased through hormone replacement . Steroid hormones also influence NGF.…”
Section: R49mentioning
confidence: 99%
“…BDNF, E 2 and P measurements in FF FF BDNF level was determined by enzyme-linked immunosorbent assay (ELISA) method (BDNF Emax Immunoassay System, Promega, USA) as previous described [11,12]. Briefly, the samples were diluted with Block & Sample Buffer.…”
Section: Ff Collectionmentioning
confidence: 99%